Quantitative Evaluation of Mitochondrial Dynamics During Maintenance of Cellular Bioenergetics Using ImageJ - Mehrotra, Arpit; Sood, Abhilasha; Kanwar, Diksha (Scripta Medica, 2024)
Background/Aim: Mitochondria are one of the most dynamic organelles essential for maintaining cellular energy demands, including execution of several vital cellular processes. This feature is attributed to rapid adaptation in morphological features which dictates their functionality. Depending on the cellular status, mitochondria can be rod shaped, branched, spherical, inter-connected or can exist as a network. Aim of this study was to analyse mitochondrial morphological appearance under normal vs stress condition in mitochondria.Methods: The study evaluated mitochondrial morphology under normal and experimentally generated cellular stress condition by utilising ImageJ software, a versatile image analysis tool. Live-cell imaging technique was employed to capture high-resolution images of mitochondrial dynamics in SH-SY5Y cells and subsequent ultra-structural changes were evaluated using transmission electron microscopy. The images were later processed using ImageJ software, with inbuilt plugins designed for image processing. Results: The present study identified alterations in mitochondrial morphology ranging from elongated, rod and interconnected mitochondria indicative of healthy mitochondrial network in controls to punctate, large/rounded and fragmented mitochondria in stress induced treated condition. Moreover, transmission electron microscopy confirmed significant abberation of  mitochondrial structure with disapperance of outer mitochondrial membrane, decrease in  matrix space and increase in mitochondrial size, with concomittant decrease in the cristae length and simultaneous increase in cristae lumen width in treated sections. Conclusion: The study implicates existence of a mutual association between mitochondrial morphology and execution of cellular functions occurring during several pathological conditions, including neurodegenerative disorders. Furthermore, by utilising such a tool for quantitative analysis, a deeper understanding of mitochondrial dynamics and potential advancement in development of mitochondria-targeted drugs is suggested.